Factors Influencing Customer Satisfaction in Health Insurance: A comprehensive study in Bengaluru, India - Chyavana Kondapally; M Vikram Reddy; B Mohan Kumar (Asia Pacific Journal of Health Management)
Objective: This paper focuses on the multifaceted dimension of customer satisfaction in health insurance within Bengaluru city. Bengaluru city is a metropolis in India with a diversified population with diverse insurance preferences, and healthcare requirements. Through this comprehensive study, we strove to analyze the impact of demographic features and health insurance benefits on customer satisfaction.